Eating disorders in children and adolescents with autism spectrum disorder (ASD) (Research, Society and Development, 2022)
Autism Spectrum Disorder (ASD) is a disorder that generates atypical neurodevelopment, affecting several aspects, generating deficits in communication and social interaction, turning patterns of behaviors, activities and interests into restricted, repetitive and stereotyped activities that generate an atypical response. to sensory stimuli. Such an atypical response, which can be presented in an exaggerated way or even by the lack of it, has a direct influence on daily activities, especially on the diet of its patients. Eating problems arising from the characteristics of the disorder, focusing on children and adolescents with ASD, present themselves as a common condition and can interfere with health, development and even in the interpersonal relationships of family members. This literature review study aimed to highlight the most prevalent eating disorders and how they affect the quality of life of these individuals. Finally, it is evident that more studies are needed in the area to encourage better tools and multidisciplinary treatments on a regular basis, in order to control the growing increase in eating disorders in this public.